Effectiveness of a no-cost-to-workers, slip-resistant footwear program for reducing slipping-related injuries in food service workers: a cluster randomized trial - Bell, Jennifer L.; Collins, James W.; Chiou, Sharon (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVE ': 'This study evaluated the effectiveness of a no-cost-to-workers, slip-resistant footwear (SRF) program in preventing workers’ compensation injury claims caused by slipping on wet or greasy floors. ' ' METHODS ': 'The study population was a dynamic cohort of food service workers from 226 school districts’ kindergarten through 12th grade food service operations. A two-arm cluster randomized controlled study design was implemented, with school districts randomized to the intervention group receiving SRF. Data were analyzed according to the intent-to-treat principle. Logistic regression was used to analyze dichotomous response data (injured based on workers’ compensation injury claims data, or not injured, for each month worked). Changes in slipping injury rates from baseline to post-intervention follow-up periods were compared between treatment groups. ' ' RESULTS ': 'The probability of a slipping injury was reduced significantly in the intervention group, from a baseline measure of 3.54 slipping injuries per 10 000 worker-months to 1.18 slipping injuries per 10 000 worker-months in the follow-up period [adjusted odds ratio (ORadj) 0.33, 95% confidence interval (CI) 0.17–0.63]. In the control group, slipping injuries were 2.01 per 10 000 worker-months in the baseline, and 2.30 per 10 000 worker-months in the follow-up. The interaction between treatment group and time period (baseline or follow-up) indicated that the decline seen in the intervention group was significantly different than the increase seen in the control group (ORadj 0.29, 95% CI 0.11–0.74, adjusted for age >55 years). ' ' CONCLUSIONS ': 'This study provides evidence for the effectiveness of a no-cost-to-workers SRF program in reducing slipping-related workers’ compensation injury claims in food service workers.
Keywords: cluster randomized trial; effectiveness; fall; food service; food service worker; footwear; kitchen; logistic regression; occupational; posttest; pretest; RCT; slip-resistant footwear; slip; trip and fall; slipping-related injury; workplace accident; workplace injury